Glycyrrhizic Acid Reduces Heart Rate and Blood Pressure by a Dual Mechanism - Kailash Singh; Aung Moe Zaw; Revathi Sekar; Ahuja Palak; Ahmed A. Allam; Jamaan Ajarem; Billy K. C. Chow (Molecules, 2016)
Beta adrenergic receptors are crucial for their role in rhythmic contraction of heart along with their role in the pathological conditions such as tachycardia and high risk of heart failure. Studies report that the levels of beta-1 adrenergic receptor tend to decrease by 50%, whereas, the levels of beta-2 adrenergic receptor remains constant during the risk of heart failure. Beta blockers—the antagonistic molecules for beta-adrenergic receptors, function by slowing the heart rate, which thereby allows the left ventricle to fill completely during tachycardia incidents and hence helps in blood pumping capacity of heart and reducing the risk of heart failure. In the present study, we investigate the potential of glycyrrhizic acid (GA) as a possible principal drug molecule for cardiac arrhythmias owing to its ability to induce reduction in the heart rate and blood pressure. We use in vitro and in silico approach to study GA′s effect on beta adrenergic receptor along with an in vivo study to examine its effect on heart rate and blood pressure. Additionally, we explore GA′s proficiency in eliciting an increase in the plasma levels of vasoactive intestinal peptide, which by dilating the blood vessel consequently, can be a crucial aid during the occurrence of a potential heart attack. Therefore, we propose GA as a potential principal drug molecule via its potential in modulating heart rate and blood pressure.